cDNA cloning of Batis maritima methyl chloride transferase and purification of the enzyme - Ni, Xinhai (The National Academy of Sciences, 1998)
Methyl chloride transferase catalyzes the synthesis of methyl chloride from S-adenosine-l-methionine and chloride ion. This enzyme has been purified 2,700-fold to homogeneity from Batis maritima, a halophytic plant that grows abundantly in salt marshes. The purification of the enzyme was accomplished by a combination of ammonium sulfate fractionation, column chromatography on Sephadex G100 and adenosine-agarose, and TSK-250 size-exclusion HPLC. The purified enzyme exhibits a single band on SDS/PAGE with a molecular mass of approximately 22.5 kDa. The molecular mass of the purified enzyme was 22,474 Da as determined by matrix-associated laser desorption ionization mass spectrometry. The methylase can function in either a monomeric or oligomeric form. A 32-aa sequence of an internal fragment of the methylase was determined (GLVPGCGGGYDVVAMANPER FMVGLDIXENAL, where X represents unknown residue) by Edman degradation, and a full-length cDNA of the enzyme was obtained by rapid amplification of cDNA ends–PCR amplification of cDNA oligonucleotides. The cDNA gene contains an ORF of 690 bp encoding an enzyme of 230 aa residues having a predicted molecular mass of 25,761 Da. The disparity between the observed and calculated molecular mass suggests that the methylase undergoes posttranslational cleavage, possibly during purification. Sequence homologies suggest that the B. maritima methylase defines a new family of plant methyl transferases. A possible function for this novel methylase in halophytic plants is discussed.